Felix Ter-Martirosov - Mikayelyan, Lilit (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
Felix Ter-Martirosov was born in Tbilisi in 1939, in the district of Sololak, which had a large Armenian population. There he attended a Russian middle school. During his school years he became acquainted with the Georgian archaeologist I. A. Gzelishvili. He began to participate in summer excavations led by Gzelishvili and became interested in archaeology. Gzelishvili advised him to continue his education in Moscow. In 1958, upon graduating from school, he was drafted into the Soviet Army.